APPLICATION OF VINEGAR AS BIOPRESERVATIVE TO INHIBIT Salmonella typhimurium IN FRESH CHICKEN MEAT - Juniawati Juniawati; Miskiyah Miskiyah; Widaningrum Widaningrum (Buletin Peternakan, 2017)
Using natural preservative is a choice amid fears consumers to use a chemical preservative in food products including fresh meat. Acetic acid can be used as a preservative because of its ability to inhibit the growth of microbes. However, a strong smell and taste of the synthetic acetic acid limit its use in food products. This research aims to determine the ability of acetic acid from banana peel vinegar and coconut water vinegar to inhibit the growth of Salmonella typhimurium in fresh meat. The study was conducted at two storage temperature are room temperature and temperature of 5-7°C where at each temperature is designed using completely randomized design with acid treatments (vinegar banana peel vinegar, coconut water vinegar, acetic acid and lactic acid commercial) and repeated in triplicates.  Sample 75 g that has been treated with acid soaking, inoculated with Salmonella, allowed until 20 minutes, packed and put at room temperature and refrigerated temperature.The result showed that banana peel vinegar is the most effective for reducing Salmonella typhimurium than coconut water vinegar, commercial acetic acid, and commercial lactic acid up to 24 hours at room temperature.  Coconut water vinegar is the most effective for reducing Salmonella typhimurium up to 12 days of storage at temperature 5-7°C.